Turkey : Second Review Under the Stand-By Arrangement-Staff Report; Staff Statement; News Brief on the Executive Board Discussion; and Statement by the Authorities of Turkey. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper evaluates Turkey's Second Review Under the Stand-By Arrangement (SBA). Since the completion of the Article IV Consultation and the first review in April 2002, macroeconomic policies have remained in line with the program. All quantitative performance criteria for end-March and end-April have been met. In light of continued strong program implementation, the IMF staff recommends the completion of the second review. Strict implementation has already produced tangible economic gains, and the authorities are determined to stay the course.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet